Micro et nanoparticules magnétiques à base de polysaccharides modifiés pour le transport à cible des médicaments antitumorales - ZANOUNE, Kheira (l’Université de Mostaganem, 2022)
Cancer remains one of the world’s most devastating diseases, responsible for more than 20% of all deaths that is defined as uncontrolled proliferation of cells and rapidly spread to healthy tissues. Controlled drug delivery systems offers great opportunities for the development of new non-invasive strategies for the treatment of cancers and the main advantage of these systems is represented by their capacity to accumulate in tumors by enhanced permeability and retention effect. As part of this thesis work, innovative hybrid drug delivery systems, based on a polymer containing both magnetic nanoparticles as well as an antitumoral drug, was developed in order to improve the efficiency of the antitumoral treatment. We focused our research on two types of hybrid magnetic nanoparticles: nanocapsules obtained by the interfacial condensation between chitosan and poly(N-vinyl pyrrolidone-alt-itaconic anhydride) and magnetic nanospheres based on chitosan obtained by double crosslinking in reverse emulsion. The hybrid nanoparticles (nanocapsules and nanospheres) formed is characterized in order to determine their shape and size; these particles are from a few tens to a few hundred nanometers in diameter. SEM confirmed their nanometric size and their well-defined spherical shape. These nanocapsules and nanospheres allowed the encapsulation of an increased amount of 5-Fluorouracil and presented a controlled drug release. In vitro studies have revealed that these drug-loaded hybrid nanocapsules were able to induce a cytostatic effect on breast carcinoma MCF7 cell, comparable to that of free drug.
Keywords: hybrid nanocapsules; hybrid nanospheres; smart hybrid nanocapsules; hybrid nanospheres; smart polymers; magnetic nanoparticles; 5-Fluorouracil; antitumoral therapy; breast carcinoma; magnetic nanoparticles; 5-Fluorouracil; antitumoral therapy; breast carcinoma.